Three-phase electrical power - Fleckenstein, Joseph E. (CRC Press, 2016)
"Three-Phase Electrical Power addresses all aspects of three-phase power circuits. The book treats the transmission of electrical power from the common sources where it is generated to locations where it is consumed. At typical facilities where electrical power is used, the book covers the important topics of grounding, currents, power, demand, metering, circuit protection, motors, motor protection, power factor correction, tariffs, electrical drawings, and relays. Included in the text are the necessary methods of computing currents and power in all possible types of circuit applications as those that are balanced, unbalanced, leading, lagging, three-wire, and four-wire. Focusing on electrical gear, programs, and issues related to the generation and use of three-phase electrical power, this contemporary educational guide:Uses simple, straightforward language to explain key concepts and their underlying theoryIntroduces numerous examples, illustrations, and photographs to aid in comprehensionEmploys phasor concepts throughout the text to aid in the analysis of three-phase circuitsEncourages applied learning by supplying practical problems at the end of each chapterProvides extensive references and a glossary of symbols, acronyms, and equationsThree-Phase Electrical Power delivers a much-needed modern-day treatment of three-phase electrical power for electrical engineering students and practitioners alike."--Provided by publisher.